Budidaya Ikan dan sayur dalam Ember Menggunakan Konsep Matematika untuk UMKM Muria 34 yang Kompeten - Al Ayubi, Sholahuddin; Purwandhini, Ari Septianingtyas; Mujib MT, A. (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
This community service program aimed to enhance the knowledge and skills of the MURIA 34 Community Group in Bondowoso Regency in developing food security–based enterprises through the implementation of Budidaya Ikan dan Sayur dalam Ember (BUDIKDAMBER) or fish and vegetable cultivation in buckets. The activities employed participatory and educational methods, including socialization, training, hands-on practice, and mentoring. The program was conducted on Friday, October 23, 2025, involving approximately 20–25 participants, from 08:00 a.m. to 03:30 p.m. The participants received materials on catfish cultivation, water spinach cultivation, integrated BUDIKDAMBER systems, business management, and digital marketing. The results indicate an improvement in participants’ understanding and practical application of integrated cultivation techniques and small business management. The program outcomes included 22 bucket ponds (20 cylindrical and 2 rectangular), 500 catfish fingerlings, water spinach seeds, and fish feed for field practice. Overall, this program successfully increased community awareness and independence in supporting household food security and encouraged the development of competent and sustainable micro, small, and medium enterprises (MSMEs).